The Influence of Store Image on Purchasing Decisions with Purchase Intention as an Intervening Variable: (Empirical Study on Alfamart Consumers in Semarang) - M. Trihudiyatmanto; Bambang Dewantoro (Journal of Economics, Management, and Business, 2025)
Purpose - This study aims to determine the effect of store image on purchasing decisions through purchase interest in Alfamart consumers in Semarang. Design/methodology/approach - This study is a quantitative study. The population in this study were Alfamart consumers in Semarang. The sampling technique used non-probability sampling with a sample size of 104 respondents. The data collection technique used a questionnaire, which had been tested for validity and reliability. The data analysis technique used to answer the hypothesis was Structural Equation Modeling (SEM). Findings - The results of this study indicate that: (1) Store image has a positive and significant effect on Purchase Interest, (2) Store Image has a positive and significant effect on Purchase Decisions through Purchase Interest, (3) Store Image has a positive and significant effect on Purchase Decisions, (4) Purchase Interest has a positive and significant effect on Purchase Decisions. This is evidenced by the Purchase Interest mediation coefficient of 1.099 which is greater than the direct effect of 0.514 so that the Purchase Interest variable is proven to be able to mediate the effect of Store Image on Purchase Decisions.